The ‘Platformisation’ of Domestic Work in South Africa - Tengetile Nhleko (The Thinker)
Digital platform technologies have brought about a new labour form in the occupation of domestic work, in which domestic cleaning work is now being managed and organised virtually through an online platform, or ‘app’, operated by private technology companies and provided to householders on a convenient and on-demand basis. This paper analyses the emerging impact of this new form of ‘platform domestic work’ in South Africa’s domestic sector using an interpretivist case study done in Cape Town on ten platform domestic workers and their platform companies. Using evidence obtained through in-depth interviews and analysis of published company discourse material, this paper argues that far from formalising and modernising domestic work through the twin forces of commercialisation and digital platform technology, the phenomenon of platform domestic work is deepening informalisation in paid domestic work as a form of insecure ‘gig work’, and also through the widespread practice of platform leakage by domestic workers on the platform.